De Nederlandse Gezondheidszorg 2014
DOI: 10.1007/978-90-368-0705-0_8
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent and founder mutations in the Netherlands: mutation p.K217del in troponin T2, causing dilated cardiomyopathy*

Abstract: orIgInAl ArtIcle recurrent and founder mutations in the netherlands: mutation p.K217del in troponin t2, causing dilated cardiomyopathy Background. About 30% of dilated cardiomyopathy (DCM) cases are familial. Mutations are mostly found in the genes encoding lamin A/C, beta-myosin heavy chain and the sarcomeric protein cardiac troponin-T (TNNT2). Mutations in TNNT2 are reported in approximately 3% of DCM patients. The overall phenotype caused by TNNT2 mutations is thought to be a fully penetrant, severe disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…; Otten et al . ). Mutations in the non‐sarcomeric gene LMNA , encoding the inner nuclear protein lamin A/C, have been found in 6% of DCM patients (Parks et al .…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…; Otten et al . ). Mutations in the non‐sarcomeric gene LMNA , encoding the inner nuclear protein lamin A/C, have been found in 6% of DCM patients (Parks et al .…”
Section: Introductionmentioning
confidence: 97%
“…Truncation in this part of the protein would cause loss of the cTnC and two actin-binding domains of cTnI (Mogensen et al 2015). The p.K217del (also known as p.K210del; Otten et al 2010) mutation in the TNNT2 gene has been reported across the world in unrelated families and is associated with high mortality and disease onset at a young age (ß33 years) (Kamisago et al 2000;Mogensen et al 2004;Hershberger et al 2009;Otten et al 2010). Mutations in the non-sarcomeric gene LMNA, encoding the inner nuclear protein lamin A/C, have been found in 6% of DCM patients (Parks et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, particular mutations in four other loci have been reported to partially phenocopy ARVC/D-DESMIN, TITIN, LAMIN A/C, and PHOSPHOLAMBAN [Klauke et al, 2010;Otten et al, 2010;Taylor et al, 2011;Quarta et al, 2012;Van Der Zwaag et al, 2012;Lorenzon et al, 2013] with fibro-fatty replacement being seen in the TITIN and LAMIN A/C cases, although most mutations in these four loci do not preferentially affect the RV.…”
Section: Introductionmentioning
confidence: 99%
“…Por último, una variante de muy mal pronóstico (p.Lys210del), con una sobrevida ligeramente superior a 80% a los 20 años (casi un 20% de los individuos habían sufrido una muerte cardiovascular a esta edad); la sobrevida solo llegaba a 30% a los 60 años. Hay que remarcar que el fenotipo predominante en esta última variante es MCD, y un gran número de las muertes cardiovasculares se deben a fallo cardíaco o trasplante (52) .…”
Section: ) Valor Pronósticounclassified